A atividade piscícola em tanques-rede no Reservatório de Itaipu: o caso da comunidade indígena Tekoha Ocoy - Orsi, Magali Rozangela Stempniak (2011)
The sustainable use of natural resources, particularly in the case of fishery resources is a challenge that must be seen in terms of technical, political, economical and social, and Brazil is one of the few countries where inland fishery has a considerable economic value, which emphasizes the cultivation of fish in cages, allowing rivers and hydroelectric reservoirs been utilized not only for power generation. In this context fits Tekoha Ocoy, Ava-Guarani indigenous, allocated in São Miguel do Iguaçu at Paraná state and affected by dam construction for installation of the Itaipu Hydroelectric Plant. Thus, this work was characterized by a case study and survey data on fish farming in cages in this indigenous community, assisted by the Cultivando Água Boa Project, developed by Itaipu Binacional aims to promote social inclusion, recovery and enhancement of indigenous communities in the Bacia do Paraná 3 (BP3), providing better quality of life for these communities. It was found that the program, and its proposes, is not meeting the needs of the indigenous community, even showing its support to the implementation of the program, expressed no satisfaction over the results achieved and the manner of its execution, according to the data collected in the development of this research. The results obtained showed that fish culture in cages for this community in question can be a great lever of social, economic and cultural development, enabling the effective use of natural local resources, yet respecting the views of affected and the environment. For this, the activity should be planned considering the characteristics of community areas where it is deployed, been necessary to harmonize the production process with the local culture and environment, to become a viable alternative to sustainable development.